The Mythology and Theology of Love in Spenser's Amoretti. Issue 2 (17th February 2017) - Cousins, A. D.
ABSTRACT: Edmund Spenser depicts his courtship, in his sonnet sequence Amoretti, by means of an immanent mythological and mythographic patterning more elaborate and specific than has been hitherto acknowledged. Through this patterning, Spenser suggests that his courtship does not merely evoke but necessitates metamorphosis, in both the beloved who represents Elizabeth Boyle, his intended, and the lover who represents himself. As the title of his sequence indicates, Spenser connects transformation of the lady, whom he identifies at first as a donna angelica, with the mythology and mythography of Cupid. Inseparable from his doing so—and of greater subtlety—is his portraying her in association with the mythology as well as mythography of Venus. He likewise links the transformation required of his persona with the figure of Cupid; nonetheless, with greater subtlety he associates his persona with the figure and lore of Ulysses. Impelling their mutually interactive transformations, Spenser intimates, is an experience of love where eros and agape meet in eventual and unstable harmony as caritas . That is to say, a distinct theology of love informs the mythic design of Amoretti .